2017
DOI: 10.3389/fnins.2017.00526
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Error Augmentation on Brain Activation and Motor Learning of a Complex Locomotor Task

Abstract: Up to date, the functional gains obtained after robot-aided gait rehabilitation training are limited. Error augmenting strategies have a great potential to enhance motor learning of simple motor tasks. However, little is known about the effect of these error modulating strategies on complex tasks, such as relearning to walk after a neurologic accident. Additionally, neuroimaging evaluation of brain regions involved in learning processes could provide valuable information on behavioral outcomes. We investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
63
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 69 publications
5
63
1
Order By: Relevance
“…As hypothesized, we found that training with error amplification resulted in better motor learning than haptic guidance. This is in line with previous studies that found that training with error amplification outperforms training with haptic guidance when the task difficulty is appropriate for subjects' initial skill level (Milot et al 2010;Marchal-Crespo et al 2014a;Duarte and Reinkensmeyer 2015;Marchal-Crespo et al 2017). This can be explained by the Challenge Point Theory, which states that optimal learning is achieved when the difficulty of the task is appropriate for the individual subject's level of expertise (Guadagnoli and Lee 2004).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As hypothesized, we found that training with error amplification resulted in better motor learning than haptic guidance. This is in line with previous studies that found that training with error amplification outperforms training with haptic guidance when the task difficulty is appropriate for subjects' initial skill level (Milot et al 2010;Marchal-Crespo et al 2014a;Duarte and Reinkensmeyer 2015;Marchal-Crespo et al 2017). This can be explained by the Challenge Point Theory, which states that optimal learning is achieved when the difficulty of the task is appropriate for the individual subject's level of expertise (Guadagnoli and Lee 2004).…”
Section: Discussionsupporting
confidence: 91%
“…playing a pinballlike game (Milot et al 2010)-but limited transfer of learning in a continuous task -e.g. tracking a Lissajous figure (Marchal-Crespo et al 2017). In the current study, all training strategies generalized learning of the continuous task game, but only subjects trained with haptic guidance generalized the continuous task game, although no significant differences between strategies were found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the CNS of people with SCI may be faster in returning to the baseline state of the MoS_Min to reduce the energy cost, resulting in a faster decline of the after effect for the varied force condition. A recent imaging study in healthy controls also indicated that different brain activation patterns were observed for the abrupt and random perturbations (Marchal‐Crespo, Michels, Jaeger, Lopez‐Oloriz, & Riener, ). Along this line of thinking, we speculate that the motor memory produced by errors with varied size and errors with consistent size may be stored in different regions of the brain, which may be a cause for the different levels of lasting of the after effect of MoS_Min.…”
Section: Discussionmentioning
confidence: 95%
“…Stroke neurorehabilitation often uses the unique aspects of technology to improve motor recovery. While some researchers endeavored to simply assist movement to more closely resemble healthy patterns [1,2,3], others have attempted to exploit unique capabilities of robotics or graphic feedback to encourage neuroplasticity by augmenting error [4,5,6,7,8]. Even some traditional physical therapy exercises use mirrors to get the paretic side of the body to imitate the non-paretic side [9].…”
Section: Introductionmentioning
confidence: 99%